Protective effects and mechanism of resveratrol in animal models of pulmonary fibrosis: a preclinical systematic review and meta-analysis - Yin, Yajie; Jia, Nan; Luo, Hui; Feng, Xinglin; He, Xin; Huang, Ju; Wang, Fei (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis (PF) is a chronic lung disease characterized by ongoing interstitial scarring. Current treatments can only slow the progression of the disease. Resveratrol (RES), a natural polyphenolic compound, has become a potential therapy for PF because of its multiple biological effects, including anti-fibrotic, anti-inflammatory, and antioxidant properties.ObjectivesTo clarify RES’s efficacy, safety, and mechanism of action in treating PF through a preclinical systematic review.MethodsA computerized search of eight databases (up to 6 March 2025) was conducted to identify in vivo animal experiments on RES treatment for PF. The SYRCLE tool was used to assess the risk of bias, and meta-analysis was performed using RevMan 5.4 and Stata 17.0. The outcome measures included two main aspects: core pathological processes and molecular mechanisms. Heterogeneity was assessed with the I2 test, and publication bias was evaluated using funnel plots and Egger’s test.ResultsA total of 25 studies were included, involving 628 animals in the experimental groups and 357 animals in the control groups. Meta-analysis of selected outcome measures showed: 1. Improved fibrosis: significant reduction in pulmonary fibrosis score (SMD = −2.30, 95% CI [−2.80, −1.79], p < 0.00001, I2 = 76%) and decreased Hyp content (SMD = −2.16, 95% CI [−2.69, −1.63], p < 0.00001, I2 = 85%); 2. Inhibited inflammation: reduced TNF-α content (SMD = −1.58, 95% CI [−2.18, −0.99], p < 0.00001, I2 = 70%) and decreased IL-6 content (SMD = −2.16, 95% CI [−2.74, −1.59], p = 0.007, I2 = 57%); 3. Restored oxidative balance: decreased MDA content (SMD = −2.22, 95% CI [−3.09, −1.35], p = 0.06, I2 = 55%) and increased SOD content (SMD = 1.67, 95% CI [1.05, 2.30], p < 0.0001, I2 = 76%).ConclusionRES significantly enhances the pathological process in PF animal models by regulating the TGF-β/Smad and NF-κB pathways. Future efforts should focus on optimizing preclinical study designs to decrease heterogeneity and improve clinical translation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/, Identifier CRD420251009847.